The effect of intermittent versus continuous enteral feeding for critically ill patients: a meta-analysis of randomized controlled trials - Qu, Jing; Xu, Xiaoya; Xu, Chaobo; Ding, Xuzhong; Zhang, Kai; Hu, Leshuang (Frontiers in Nutrition, 2023)
The effect of intermittent versus continuous enteral feeding for critically ill patients: a meta-analysis of randomized controlled trials Abstracts Objectives: The appropriate strategy for enteral feeding in critically ill patients still remains controversial. Therefore, we conducted this meta-analysis to compare the effect of intermittent versus continuous enteral feeding method for critically ill patients.Methods: Electronic databases including PubMed, Embase, Scopus, and Cochrane Library were searched up to April 10th, 2023 for randomized controlled trials evaluating the effect of intermittent versus continuous enteral feeding for critically ill patients. The primary outcomes were feeding intolerances, including diarrhea, vomiting, distension, constipation, gastric retention, and aspiration pneumonia. The secondary outcomes were mortality in intensive care unit (ICU), length of stay in ICU, and achievement of nutritional goal.Thirteen studies with a total of 884 patients were analyzed in this meta-analysis. Overall, the use of intermittent enteral feeding was associated with higher incidence of diarrhea (OR 1.66, 95%CI 1.13 to 2.43, I 2 =16%) and distension (OR 2.29, 95%CI 1.16 to 4.51, I 2 =0%), lower incidence of constipation (OR 0.58, 95%CI 0.37 to 0.90, I 2 =0%), and longer length of ICU stay (MD 1.09, 95%CI 0.53 to 1.64, I 2 =0%). Moreover, no significant difference was identified for other outcome measures.In critically ill patients, the implementation of intermittent enteral feeding was associated with higher incidence of diarrhea and distension, longer length of ICU stay, but lower occurrence of constipation. Nevertheless, the absence of sufficient high-quality randomized controlled clinical trials precludes any definitive conclusions regarding the optimal approach to enteral feeding in this population.There is an imperative need for more studies to further assess the efficacy of the two enteral feeding strategies.